Human beta cells generated from pluripotent stem cells or cellular reprogramming for curing diabetes - Randolph, Lauren N. (Regen Eng Transl Med, 2018)
Diabetes is a group of metabolic diseases characterized by aberrantly high blood glucose levels caused by defects in insulin secretion, its action, or both, which affects approximately 30.3 million people (9.4% of the population) in the United States. This review will focus on using human β cells to treat and cure diabetes because β cells are absent, due to an autoimmune destruction, in Type 1 diabetes or dysfunctional in Type 2 diabetes. In order to generate enough functional β cells for diabetes treatment (0.1 to 1 billion cells to treat one patient), a basic science approach by mimicking what happens in normal pancreatic development must be closely aligned with engineering. Two general approaches are discussed here. The first one uses human pluripotent stem cells (hPSCs) to perform directed differentiation of hPSCs to β cells. This is advantageous because hPSCs grow indefinitely, providing a virtually unlimited source of material. Therefore, if we develop an efficient β cell differentiation protocol, we can essentially generate an unlimited amount of β cells for disease modeling and diabetes treatment. The second approach is cellular reprogramming, with which we may begin with any cell type and covert it directly into a β cell. The success of this cellular reprogramming approach, however, depends on the discovery of a robust and efficient transcription factor cocktail that can ignite this process, similar to what has been achieved in generating induced pluripotent stem cells. This discovery should be possible through identifying the important transcription factors and pioneer factors via recent advances in single-cell RNA sequencing. In short, a new renaissance in pancreas developmental biology, stem cell engineering, and cellular reprogramming for curing diabetes appears to be on the horizon.